Living Abroad During COVID-19: International Students’ Personal Relationships, Uncertainty, and Management of Health and Legal Concerns During a Global Pandemic - Thorson, Allison R; Doohan, Eve-Anne M; Clatterbuck, Leah Z (Journal of International Students, 2022)
The purpose of this study was to better understand the uncertainties that international students faced and managed throughout COVID-19 and the impact these uncertainties had on their personal relationships. We conducted interviews with 14 international students and found that they were particularly uncertain about the health of their family members (RQ1a), their health (RQ1b), and where to wait out COVID-19 (RQ1c). Those uncertainties that could be navigated were managed via participants giving informational directives, providing instrumental support, making emotional appeals (RQ2a), engaging in new behaviors and self-care (RQ2b), and increasing communication with and withholding information from family members (RQ2c). Last, we found that COVID-19 impacted international students’ personal relationships in two distinct, positive, ways: they became closer with friends and connected more with family members (RQ3). Overall, the findings from our study have implications for future research and offer suggestions for supporting international students during times of future uncertainty.